Highly crosslinked polyesters prepared by ring-opening copolymerization of epoxidized baru nut and macaw palm oils with cyclic anhydrides - Vermiglio, Aaron L.; Alarcon, Rafael T.; Cavalheiro, Éder T. G.; Bannach, Gilbert [UNESP]; Farmer, Thomas J.; North, Michael (Royal Society of Chemistry (RSC), 2023)
Epoxidised Brazilian vegetable oils obtained from the baru nut (Dipteryx alata Vogel) and the macaw palm (Acrocomia aculeata) react with bioderivable anhydrides (succinic, glutaric, itaconic or citraconic) to give highly crosslinked polyesters. The polymerisation is initiated by a metal-free catalyst system comprising dicyclohexyl urea and bis(triphenylphosphine)iminium chloride. The resulting polymers can be obtained as powders or rubbery disks and are chemically and physically characterised. On treatment with aqueous sodium hydroxide, the polymers degrade to water soluble glycerol and sodium carboxylates.